The Influence of Organizational Culture and Work Motivation on the Performance of Physical Education Teachers in Medan High Schools - Mesnan Mesnan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study was to find and study: (1) the performance model of Physical Education teachers which is built based on the associative causal relationship between exogenous variables and endogenous variables. This research was conducted at Senior High Schools in Medan, involving 148 Physical Education teachers as respondents. For data collection, it was done using a questionnaire with five answer choices. The sampling technique used is proportional random sampling. The instrument used was tested first on respondents outside the sample to obtain valid and reliable instruments. The validity test uses Product Moment Correlation, while to test its reliability the Alpha formula from Cronbach. Before testing the hypothesis, the Requirements Analysis test is calculated including: data normality test and regression linearity test. Meanwhile, to test its reliability with the Alpha formula from Cronbach. The results showed (1) the Physical Education Teacher Performance Model (2) Organizational Culture has a positive direct effect on Job Satisfaction, (3) Transformational Leadership has a positive direct effect on Job Satisfaction, (4) Organizational Culture has a positive direct effect on Work Motivation, (5) ) Transformational Leadership has a positive direct effect on Work Motivation, (6) Organizational Culture has a positive direct effect on performance, (7) Transformational Leadership has a positive direct effect on performance, (8) Job Satisfaction has a positive direct effect on Performance, (9) Job Motivation has a direct effect on Performance. Positive on performance.Based on the acceptance of research hypotheses, it is found a theoretical model or fixed model that describes the structure of the causal relationship between organizational culture variables, transformational leadership, job satisfaction, work motivation, and the performance of high school Physical Education teachers in Medan City.